(untitled) (Clinical Sociology Review, 2025)
"Dialogues with Eugène Enriquez: On the Work: From the Horde to the State – Psychoanalysis of the Social Bond" is a collection organized by Vanessa Andrade Barros, Teresa Cristina Carreteiro, Jacyara Rochael Nasciutti, and José Newton Garcia de Araújo, celebrating the 40th anniversary of Eugène Enriquez’s seminal work, De la horde à l’État. The book brings together contributions from various scholars who revisit and expand on Enriquez’s ideas, integrating theoretical and practical perspectives that bridge the individual and the collective. The work is divided into two main parts: the first, "Freud and the Social Bond," explores the foundations of Enriquez’s thought, addressing themes such as myth, political power, religion, and violence. The second part, "Social Bond, Domination, and Power," examines issues of gender, culture, modern power, and contemporary challenges, such as the fragility of community ties and democratic regression. This work is essential for understanding the relevance of Enriquez’s thought and its applications in analyzing current issues, making it a must-read for researchers interested in social dynamics and power structures.